Diasporas and Armed Conflicts: beyond Being “Third Party” - I. D. Loshkariov (Vestnik MGIMO-Universiteta)
The article discusses an essential dimension of modern diaspora research related to the functional status of diasporas in contemporary armed conflicts. The conventional point of view is that diasporas can only act as the “third party” of the conflict by either contributing to the deepening of the contradictions between the opposing parties or acting as an intermediary between them. In theoretical terms, the author relies on the concept of “new” or network wars (netwars) and tries to demonstrate that there are the prerequisites for more active involvement of diasporas in armed conflicts at the structural level of modern world political processes. To identify the structural requirements for such participation, the author turns to the analysis of two cases. The first case is the emergence and functioning of the 1st Polish Corps in 1917-1918 in Russia, which was formed when the Polish population of Russia was separated from their territory of origin as a result of the First World War. An analysis of the documents shows that the leadership of the corps quite clearly evaded political subordination to the Russian authorities and retained only military subordination, implying that the task of this unit was to participate in the restoration of Polish statehood. The second case is the genesis and evolution of the “Secret Army” of General Wang Pao in Laos in 1960-1974. This unit played an essential role in the Civil War in Laos, as it managed to restrain the onslaught of the superior forces of the Patet Lao Front and troops from North Vietnam. Such long-term participation in hostilities was made possible thanks to US special services' logistical and technical support. The two case studies allow us to conclude that there were armed units in previous historical periods with a clear diaspora component: they made a significant contribution to the overall dynamics of the confrontation between major parties to the conflict. This experience helps analyze contemporary conflicts with the diaspora component, especially in the context of the gradual erosion of power resources in world politics. The participation of diasporas in armed conflicts outside the “third party” framework is associated with the achievement of several conditions, both internal and external ones.